Religious Affiliation of Children in the Draft Interreligious Laws of the Kingdom of SCS and Yugoslavia 1919–1941 - Đukić, Dalibor B (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
Following the proclamation of the unified state of the South Slavs, the process of harmonizing legislation on religious organizations across the various historical provinces that became part of the state commenced. While regulations governing the organization and functioning of specific religious organizations were only enacted after 1929, efforts to draft comprehensive legislation to regulate interreligious relations and the legal status of all religious organizations continued until 1941, when they were interrupted by the outbreak of World War II. One particularly sensitive issue addressed in these legislative drafts was the determination of children’s religious affiliation. This paper argues that, while the drafts of interreligious laws and regulations adopted several progressive and modern concepts for determining children’s religious affiliation, they simultaneously retained conservative provisions that favored recognized religions. These conservative elements reflected the broader framework of state-church relations in the Kingdom of Serbs, Croats, and Slovenes (later Yugoslavia) during the interwar period.